Improvement of natural pastures technology validation in the Southern Highlands of Santa Catarina (Revista de Ciências Agroveterinárias, 2014)
The improvement of natural pastures was consolidated in the highlands of Santa Catarina State only recently when a great area of improved natural pastures already existed. Technology adopted by farmers was due to its increase in fodder production and stocking capacity. Besides, this technology presented costs inferior to the ones for conventional pasture cultivation. However, this technology still needs a more rigorous evaluation, which is to be achieved by three on farm experiments, conducted in Campo Belo do Sul county. It was evaluated forage production and quality, animal liveweight gain (LWG) and the profitability of the native pasture improvement technology. The average results were as follows: the pastures showed an in vitro OMD of 66.1; 62.6; 72.4 and 66.5%, during summer, autumn, winter and spring season, respectively. The crude protein content was of 14.7; 19.7; 22.0 and 14.4% for the same season order. Animal LWG of 511, 63 kg ha-1 year-1 , with a daily animal LWG of 0.789 kg animal-1 day-1 and animal stocking of 648 kg of LW ha-1. Finally, the system showed an economic gross margin of R$ 811,10 ha-1 (U$ 477,00 ha-1).
Keywords: animal production; cool season species introduction; natural pasture.